Kaliskie Towarzystwo Dobroczynności (1879–1914) - Tomaszewicz, Andrzej (Przegląd Nauk Historycznych, 2006)
The first charitable society in Kalisz was founded in 1825. It's board included mostly civil seIVants of different provintial and later gubernatorial and municipal public bodies. When the Kalisz gubernatorial province ceased to exist and the civil servants left Kalisz the activity of the society froze.Stanislaw Chelmski - the chairman of the local Land Credit Society - was the main initiator of reviving the former charitable society. He convinced a group of the town's intellectuals to cooperate with him and after the approval of the statutes by the tsar in 1879 the Society resumed it's activity the following year in January.In the first few years of it's existence the Society mostly gave allowances to the poor. Gradually, however, it extended it's forms of charity. In 1884 a loan fund for tradesmen was opened. In 1890 it started a project called 'Cheap Cooking'. Two years later a common room for poor children was initiated. Later in 1902 the Society ran a nursery and in 1906 they started a primary school for needy children. There also existed free medical assistance and an employment agency.The biggest achievement of the Society was the opening of it's head office in 1900 with an orphanage, old people's home, common room, eating-house and a primary school.The income in the early years of the twentieth century was on average 11 000 rubles, but there were years in which it was higher than 15000 rubles. The flnandal resources also grew steadily in time. In 1881 it was 5309 rubles, reaching the impressive amount of 64 620 rubles in 1913.There were 362 members of the Society in 1880. The number dropped to 208 members at the end of the 19th century. In the next couple of years the number rose again but it never reached the level of 1880.Kalisz Charitable Society played an important role in the town's public life. It helped to a considerable extent to reduce areas of poverty in the very difficult time of Poland's partition, deep economic and social changes, which led to an increase of the number of the poor. Huge credit for that should be given to the town's intellectuals who administered the Society's works. Due to their commitment and efforts almost 400 town dwellers took advantage of different forms of help during the 20th century.